TEKNOLOGI PENGGUNAAN AUTOFEEDER DAN PRODUKSI TERHADAP PENDAPATAN PEMBUDIDAYA UDANG VANAME (Litopenaeus vannamei) - Yenti Rokhmulyenti; Maman Haeruman; Dety Sukmawati; Euis Dasipah; Nataliningsih Nataliningsih (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
The purpose of this study was to prove the effect of using an autofeeder on production, as well as to prove empirically the effect of using an autofeeder on income, and to prove the effect of using an autofeeder on production with intervention as a variable. The method used in this study is the Regresion method with a population of 95 vaname shrimp cultivators located in Sukabumi Regency. The results of this study indicate that the use of autofeeder, production and income of vannamei shrimp cultivation in Sukabumi Regency are in the good category, through increased production of autofeeder use which will increase the income that increases from the production of vannamei shrimp farmers in Sukabumi Regency has a positive effect on increasing production and income.